A new approach of rock tension−compression cyclic measurement. Issue 1 (12th March 2019) - Liu, J.; Wang, C.; Wu, Z.; Wang, L.; Xu, H.; Pei, J.; Deng, C.
Abstract : On the basis of the MTS815 rock mechanics test system, a new measurement set-up was developed to study the tension−compression cyclic behaviour of rocks. The new measurement set-up implements a completely reversed loading condition that is direct tensile stress loading and compressive stress loading. On the basis of the experimental observation, the developed measurement set-up can be easily applied for investigating the tension−compression cyclic behaviour of rock material. It is capable of monitoring the microcracking process by combining the developed measurement set-up and acoustic emission testing system. The axial misalignment of experimental set-up and the cylinder rigidity are the main factors affecting the availability of the new measurement method. When using this approach, the axial lines of the testing machine, the developed measurement set-up and the rock sample need to be aligned. The cylinder rigidity should be far greater than the stress level applied in the test.